Idiosyncrasies of Cultural Arts Education, Heutagogy, and Online Learning during the COVID-19 Pandemic in Indonesia - Putri, Rizki Amalia; Handayaningrum, Warih (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
This study tries to explore the origins of online learning problems in art and culture subjects in junior high schools. Furthermore, from the exploration, it is continued by understanding the idiosyncrasy that occurs in online learning and the concept of heutagogy in arts and culture education at the junior high school level. The research method is mixed-method, prioritizing qualitative aspects that are assisted by questionnaires in data collection. Data were collected using an online questionnaire through the Google Form platform for junior high school students in Pasuruan, East Java. Afterward, the data were analyzed with analytical descriptive words to see the idiosyncrasy of art and culture education with heutagogy in this COVID-19 pandemic. The results showed that the heutagogical model is a model that is deemed necessary to be developed in the era of online learning going forward. When the COVID-19 pandemic took place, the use of IT technology had the power to tailor cultural arts education for each student in accordance with the development of his generation.